The Effects of Vitamin D Supplementation on Markers Related to Endothelial Function Among Patients with Metabolic Syndrome and Related Disorders: A Systematic Review and Meta-Analysis of Clinical Trials - Tabrizi, Reza; Vakili, Sina; Lankarani, Kamran B.; Akbari, Maryam; Jamilian, Mehri; Mahdizadeh, Zahra; Mirhosseini, Naghmeh; Asemi, Zatollah (Hormone and Metabolic Research, 2018)
This systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted to summarize the effect of vitamin D supplementation on endothelial function among people with metabolic syndrome and related disorders. Cochrane library, Embase, PubMed, and Web of Science database were searched to identify related RCTs published up 20th May 2018. To check heterogeneity a Q-test and I2 statistics were used. Data were pooled by using the random-effect model and standardized mean difference (SMD) was considered as summary effect size. Twenty-two trials of 931 potential citations were found to be eligible for current meta-analysis. The pooled findings by using random effects model indicated that vitamin D supplementation to individuals with MetS and related disorders significantly increased flow-mediated dilatation (FMD) (SMD=1.10; 95% CI, 0.38, 1.81, p=0.003). However, it did not affect pulse-wave velocity (PWV) (SMD=0.04; 95% CI, –0.25, 0.33, p=0.80) and augmentation index (AI) (SMD=0.07; 95% CI, –0.25, 0.40; p=0.65). Overall, this meta-analysis demonstrated that vitamin D supplementation to patients with metabolic syndrome and related disorders resulted in an improvement in FMD, but did not influence PWV and AI.
Keywords: vitamin D supplementation; endothelial function; metabolic syndrome; meta-analysis